Putting diverse farming households’ preferences and needs at the centre of seed system development - Mausch, K.; Almekinders, Conny J.M.; Hambloch, C.; McEwan, M. (SAGE Publications, 2021)
Over recent decades international agricultural research has shown that it can generate agricultural technologies with benefits for societies in the Global South that outstrip the investments many times over. However, it has also been shown that the benefits generated are not evenly spread and do not reach some groups of farmers at all. Too often, segments of the intended target populations are left out and these often tend to be those already 'left behind'. New seeds and varieties are important elements of agricultural technologies and the development of these relies on seed delivery systems to get new varieties to the farming population. Here we argue that a clear analysis of the preferences and needs of farming households and their inherent heterogeneity is required when setting the goals for breeding programmes and designing seed delivery systems. We characterize the differences in demand profiles, which implies different types of seed delivery models that are tailed to context, crop and preferences and the multiple needs of farming households. We point to the implications for organizing and targeting the seed delivery system in order to cater for all. Recognising the existence of diverse demands, developing different seeds and varieties and delivering them through a variety of models asks for clarity on mandates and opens up the opportunities for coordination that will lead to synergies in meeting the UN's Sustainable Development Goals and reach a wider population of farming households.